2016
DOI: 10.1109/tsc.2015.2402679
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Semantic Web Service Discovery and Composition Framework

Abstract: In this paper we present a theoretical analysis of graph-based service composition in terms of its dependency with service discovery. Driven by this analysis we define a composition framework by means of integration with fine-grained I/O service discovery that enables the generation of a graph-based composition which contains the set of services that are semantically relevant for an input-output request. The proposed framework also includes an optimal composition search algorithm to extract the best compositio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(69 citation statements)
references
References 30 publications
0
68
0
1
Order By: Relevance
“…For this reason, each time the description and/or functionalities of a service are modified, the dependency graph is recomputed, from the service's layer up to the last one. In Rodríguez-Mier et al [125] the method was paired with an existing service registry utilizing Linked Data principles and semantic reasoning along with various service discovery and matchmaking configurations. It was shown that unless several indexing optimizations are incorporated, the system performs poorly; furthermore, the time required for the discovery and matchmaking phases dominates that of WSC.…”
Section: Middle Ground Methodsmentioning
confidence: 99%
“…For this reason, each time the description and/or functionalities of a service are modified, the dependency graph is recomputed, from the service's layer up to the last one. In Rodríguez-Mier et al [125] the method was paired with an existing service registry utilizing Linked Data principles and semantic reasoning along with various service discovery and matchmaking configurations. It was shown that unless several indexing optimizations are incorporated, the system performs poorly; furthermore, the time required for the discovery and matchmaking phases dominates that of WSC.…”
Section: Middle Ground Methodsmentioning
confidence: 99%
“…S k ) the subset of data i (resp. service i) belonging to L at the kth iteration of the while loop (lines [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. For all i ∈ D k ∪ S k , λ(i) equals to the optimal path value from s 0 to i on throughput criterion denoted v t (µ * (i)).…”
Section: Proof 1 the Proof Is By Induction On The Following Propertymentioning
confidence: 99%
“…These benchmarks are still used by recent approaches. For example, authors in [23] experiment their approach on WSC-08, authors in [17] on WSC-08 and WSC-09 and authors in [22] on WSC09. In the last benchmarks, a WSDL standard file [5] describes the input and output data of all the services available in the registry.…”
Section: Introductionmentioning
confidence: 99%
“…Web Service is a lightweight, independent communication technology which can receive requests from other systems [11]. To avoid requests of a point to the other point, ESB is a service transfer station.…”
Section: Application Of Soamentioning
confidence: 99%